The Role of the Ministry of Religious Affairs in Facing the Challenges of Islamic Education in the Digital Age - Roidah Lina; Qiyadah Robbaniyah; Diningrum Citraningsih; Ika Sari (Educan : Jurnal Pendidikan Islam, 2023)
This study aims to determine the role of the Ministry of Religious Affairs in facing educational challenges in the digital era. Data was collected in DIY in 5 districts—descriptive qualitative research method with data collection of interviews, observations, and documentation. The result of this research is that the Ministry of Religious Affairs of the DIY region oversees Islamic educational institutions, both formal and non-formal. Each region's Ministry of Religious Affairs has a general and special program that accommodates the needs of each area—the development of the era in the era of digitalization. The Ministry of Religious Affairs develops educational applications to facilitate Islamic educational institutions' control, supervision, and evaluation. The applications used include E-management, electronic madrasah activity plan, and budget (ERKAM), madrasah digital report card (RDM), Geschool application, E-learning, electronic learning, Jogja Digital Madrasah". (SIMBA) Management Information Systems for Early Education Assistance and Islamic Boarding Schools, Education Management Information Systems (EMIS), etc. Obstacles in implementing the transition from online to digitalization include human resources, infrastructure, and new work culture.   Keywords: The Role of the Ministry of Commerce, Challenges of Islamic Education, Alpha Generation